Factors Associated with Anxiety among Patients with Type 2 Diabetes Mellitus at Depati Bahrin Regional Hospital - Rosida Rosida; Nova Maudiana (Genius Journal, 2026)
Introduction: Diabetes mellitus is a chronic non-communicable disease characterized by persistent hyperglycemia and increasing prevalence worldwide, including in Indonesia. The rising number of cases has led to various physical and psychological complications, with anxiety being a common problem among patients with type 2 diabetes that can affect treatment adherence and quality of life. Preliminary observations at Depati Bahrin Sungailiat Regional Hospital indicated that many patients experienced anxiety related to complications, long-term treatment, and lifestyle changes. Therefore, this study aimed to identify factors associated with anxiety in patients with type 2 diabetes. Objective: This study aims to determine the association between quality of life, spirituality, and family support and anxiety levels among patients with Type 2 Diabetes Mellitus at Depati Bahrin Regional Hospital, Sungailiat, in 2025. Method: This study used a cross-sectional design. The research was conducted by distributing questionnaires to 73 respondents at Depati Bahrin Regional Hospital, Sungailiat, from November 26 to November 28, 2025. The collected data were then analyzed using univariate and bivariate analysis with the chi-square test. Result: The results of this study show that there is a relationship between quality of life and anxiety (p-value = 0.000 < 0.05), spirituality (p-value = 0.000 < 0.05), and family support (p-value = 0.000 < 0.05) and the incidence of anxiety in Type2 DM patients at Depati Bahrin Regional Hospital, Sungailiat, in 2025. Conclusion: It is expected that Depati Bahrin Regional Hospital can adopt a holistic approach to the prevention and management of Type 2 DM. The institution needs to provide anxiety management programs that include psychological counseling, cognitive-behavioral   therapy,   and   relaxation   activities   such   as   yoga   and meditation to help reduce anxiety.